A NOTE ON THE ETIOLOGY OF EPIDEMIC POLIOMYELITIS - Amoss, Harold L. (The Rockefeller University Press, 1914)
The globoid bodies, or minute microörganisms, cultivated from the central nervous organs of human beings and monkeys that have succumbed to poliomyelitis, may be detected in the incubated brain tissues of infected monkeys in forms indicating post-mortem multiplication. Incubating the poliomyelitic tissues in kidney-ascitic fluid culture medium and then crushing them is a more certain method for obtaining cultures of the organism. Identical bodies have been detected in blood films prepared on the twelfth day of the acute attack, from a paralyzed poliomyelitic monkey inoculated intraspinously. The same organism has been cultivated from the blood of a monkey that had received intravenously a large dose of a Berkefeld filtrate of poliomyelitic virus. No other microörganisms were detected either in the sections of the brain or in film preparations of the blood. These observations tend therefore to confirm the etiological relationship between the minute microörganism and epidemic poliomyelitis suggested by the successful cultivation and inoculation experiments reported by Flexner and Noguchi.